Online monitoring of Fenton‐mediated reactive red 6B oxidation kinetics. Issue 4 (20th January 2015) - Xu, Hang; Yu, Tianlong; Wang, Jianxu; Li, Mei; Liu, Yana
<x xml:space="preserve">Abstract</x> Online spectrophotometric technology was used to monitor the Fenton oxidation of the model dye Reactive Red 6B (RR6B) in an aqueous solution. The results showed that online monitoring technology was well equipped to record detailed information during the Fenton process. RR6B was successfully decomposed by Fenton oxidation and it was determined that optimal experimental conditions yielded nearly 100% dye removal to be 3.5 × 10−5 M ferrous ion, 2.5 × 10−3 M hydrogen peroxide and 3.85 pH. Both first‐order and Behnajady–Modirshahla–Ghanbery kinetics models described the Fenton process well with correlation coefficients above 0.99. The instant concentration of hydroxyl radicals and the reaction rate at different conditions were also calculated based on the above two models. © 2015 American Institute of Chemical Engineers Environ Prog, 34: 1019–1027, 2015